Coherent Spin Transport and Suppression of Spin Relaxation in InSb Nanowires with Single Subband Occupancy at Room Temperature. Issue 21 (22nd July 2014) - Bandyopadhyay, Saumil; Hossain, Md. Iftekhar; Ahmad, Hasnain; Atulasimha, Jayasimha; Bandyopadhyay, Supriyo
<x xml:space="preserve">Abstract</x> A longstanding goal of spintronics is to inject, then coherently transport, and finally detect electron spins in a semiconductor nanowire in which a single quantized subband is occupied by the electrons at room temperature. Here, the achieving of this goal in electrochemically self‐assembled 50‐nm diameter InSb nanowires is reported and substantiated by demonstrating both the spin‐valve effect and the Hanle effect. Observing both effects in the same sample allows one to estimate the electron mobility and the spin relaxation time in the nanowires. It is found that despite four orders of magnitude degradation in the mobility compared to bulk or quantum wells and a resulting four orders of magnitude increase in the Elliott‐Yafet spin relaxation rate, the spin relaxation time in the nanowires is still about an order of magnitude longer than what has been reported in bulk and quantum wells. This is caused by the elimination or suppression of the D'yakonov‐Perel' spin relaxation through single subband occupancy. These experiments shed light on the nature of spin transport in a true quantum wire and raise hopes for the realization of a room‐temperature Datta‐Das spin transistor, where single subband occupancy is critical for optimum performance.